Practical semiglobal uniform exponential stability of nonlinear nonautonomous systems - Kicha, A.; Hammami, M. A.; Abbes, I.-E. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9 We solve the following twofold problem: In the first part, we deduce Lyapunov sufficient conditions for practical uniform exponential stability of nonlinear perturbed systems under different conditions for the perturbed term. The second part presents a converse Lyapunov theorem for the notion of semiglobal uniform exponential stability for parametrized nonlinear time-varying systems. We establish the possibility of application of a perturbed parametrized system, by using Lyapunov theory, to the investigation of the robustness properties that may provide practical semiglobal uniform exponential stability with respect to perturbations.